Land suitability analysis for installing new petrol filling stations using GIS - Khahro, S.H. (Elsevier Ltd, 2014)
Sustainability of the projects is the major concern of the developers in the developing countries. It has been evident that development activities have high potential to cause damage to the environment. The rapid growth of urbanization has created greater demand for vehicles, which results in more fuel consumption. APetrol Filling Station(PFS) is the place catering this fuel need. A PFS is an important but meanwhile it is a hazardous facility, so special attention is required for its site selection. Existing land suitability approaches doesn't meet all the environmental consequences. Therefore, this study comes up with the concept of Geographical Information System (GIS)-based land suitability analysis using Analytic Hierarchy Process(AHP) as a Multi Criteria Decision Making (MCDM) technique. This would be an effective approach for viable site selectionof PFS, which will incorporate the entire environmental selection factors essential to be considered in the site selection of PFS in practice. This land suitability approach can also be extended for other development projects infuture. Â© 2014 The Authors. Published by Elsevier Ltd.